A framework for the mediation effect of comprehensive training motivation. - Abdul Aziz, Siti Fardaniah; Ahmad, Shamsuddin; Zainal Abiddin, Norhasni; Mohd Noah, Sidek; Abu Samah, Bahaman (2011)
Recent studies have highlighted training motivation as the most important precursor to training effectiveness. However, the existence of various forms of training motivation makes it difficult to accurately determine the effects of motivation in training. Therefore, a framework for the mediation effect of comprehensive training motivation on the relationships between supports from trainees, training programs, and organizational characteristics and training effectiveness is developed. The difference between this and previous frameworks is that this framework provides a more concise and comprehensive method to explain the mediation effect of overall training motivation. With this framework, it will be easier to predict training effectiveness.